A Comparative Analysis of Factors Affecting Uncontrolled Asthma among Paediatric Population in Urumqi vs Islamabad: Factors Affecting Uncontrolled Asthma among Paediatric Population - Arif, Muhammad Imran; Ru , Liang; Wang, Yanan (Pakistan Journal of Health Sciences, 2023)
The prevalence of paediatric asthma, a serious worldwide health issue, varies greatly across different geographical areas. Particularly striking contrasts have been found between Islamabad, Pakistan, and Urumqi, China, prompting a comparison of the underlying causes of uncontrolled asthma. Objective: To determine and evaluate the variables influencing uncontrolled asthma in children in the populations of Urumqi and Islamabad. Methods: A comparative cross-sectional study on children with uncontrolled asthma aged 3 to 18 years old was carried out in Urumqi, China, and Islamabad, Pakistan. Analysis of hospital data were used to evaluate the uncontrolled factors related to patient’s demographics, medical history, factors related to asthma control and living conditions and the environment. Results: In both cities, the study found important causes of uncontrolled asthma. Poor inhaler technique, raised BMI, environmental triggers such pollen allergies, poorly ventilated homes, and treatment non-compliance were also noted in both populations. In addition, the study indicated that uncontrolled asthma was present in 32% of paediatric patients in Urumqi and 56% of those in Islamabad for a variety of reasons. Conclusions: The results underscore the importance of context-specific interventions in managing paediatric asthma. Measures such as improving inhaler techniques, ensuring treatment compliance, healthy BMI and proper ventilation can significantly improve asthma control in paediatric populations of both Urumqi and Islamabad.